Employability and mobility in the "new career" with sex as the moderator / Rachel Samuel and Roaimah Omar - Samuel, Rachel; Omar, Roaimah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The “new career” is seen as moving away from the traditional career. Literature on career gives prominence to this area of study as new challenges are faced in terms of globalization and liberalization of the trade markets. The respondents were 152 Masters in Business Administration (MBA) graduates who have been employed for a minimum of three years after their MBA and are currently employed in the manufacturing or service sectors. Data were collected via questionnaires. The changes in the attitude of men towards physical mobility were obvious where they portrayed a stronger attitude towards keeping their current job than moving beyond boundaried. Career mobility in terms of external, functional and organizational mobility was more obvious after obtaining the MBA. Women portrayed a lower boundaries mindset compared to men in relation to mobility mindset and organizational preferences. In the light of future global trends, this study sheds some light for employees on the importance of employability in maintaining their current job and pursuing future options.